2003
DOI: 10.1016/s0925-4439(03)00037-1
|View full text |Cite
|
Sign up to set email alerts
|

Betaine homocysteine methyltransferase: gene cloning and expression analysis in rat liver cirrhosis

Abstract: It has been known for over half a century that homocysteine levels are elevated in liver cirrhosis, but the basis for it is not fully understood. Using differential display, we identified betaine homocysteine methyltransferase (BHMT) as a gene down-regulated in rat liver cirrhosis and most likely involved in this dysregulation. A partial BHMT clone was isolated by screening of a cDNA library with the differential display fragment. The full-length gene was generated by primer extension of cDNA. Expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It has been shown that down-regulation of Bhmt and Cth impairs conversion of homocysteine to methionine and cysteine, respectively, resulting in increased homocysteine levels in the cell (Torres et al, 1999;Forestier et al, 2003). Homocysteine accumulation is associated with impaired liver function, necrosis, liver cirrhosis, and fibrogenesis (Torres et al, 1999;Finkelstein, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that down-regulation of Bhmt and Cth impairs conversion of homocysteine to methionine and cysteine, respectively, resulting in increased homocysteine levels in the cell (Torres et al, 1999;Forestier et al, 2003). Homocysteine accumulation is associated with impaired liver function, necrosis, liver cirrhosis, and fibrogenesis (Torres et al, 1999;Finkelstein, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This NO induced inactivation is related to its binding capacity to cobalt moiety of vitamin B12 (Danishpajooh et al, 2001;Brouwer et al, 1996). A recent report by Forestier et al demonstrated that the expression and activity of betaine homocysteine methyltransferase (BHMT) decrease in biliary cirrhosis (Forestier et al, 2003) and these further prevent the remethylation process. So, according to the mentioned evidences, there is a complex interaction between different factors, which can lead to decreased Hcy utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased BHMT mRNA and protein levels were observed in cirrhotic patients and animal models, the strongest effect being observed upon HCV [98,99].…”
Section: Pathological Implications Of Bhmtmentioning
confidence: 98%